COMPARISON STUDY ON GREEN AND SUSTAINABLE BUILDING POLICIES IN DEVELOPED AND DEVELOPING COUNTRIES - I. J ONUOHA; S.A. OKEAHIALAM (Journal of Construction Project Management and Innovation)
Political authorities in developing countries of Africa have begun to develop plans that will address green and sustainable buildings, a matter and issue on which developed countries have had far-reaching experience. This study analyzed literatures on United States of America and Netherlands green building policies in order to identify important lessons that might be relevant for the development of such policies in two developing African countries namely: Nigeria and South Africa. United States of America and Netherlands were chosen because of their progression and long history of green building policies which could have practical utility to Nigeria and South Africa's green building policies. Through comparative study on green and sustainable building policies in United States of America and Netherlands, the study revealed that developed countries have more elaborate and robust green and sustainable building policies and implementation programmes that could have practical utility for green building developers and investors than developing countries. The study concluded that emerging countries could in addition to learning from the provisions of the United States of America and Netherlands green building policies adopt stronger research agenda for green and sustainable building policy issues and regulations. Based on the findings and conclusions drawn, the following recommendations have among others been proffered. That government intervention at the Federal level in Nigeria and South Africa is necessary to ensure sustainable green building policy formulation and implementation, and that efforts should be made by South Africa and Nigeria in particular to increase sensitization on the benefits of sustainable green building features among developers and investors and the public.